An integrative approach for the implementation of a management system for safety and impacts of visitation in protected natural areas - Lopez-Richard, Victor; Cassiano, Andréia Márcia; Aguiar, Rodrigo José Silva (Revista Turismo em Análise, 2020)
The management of visitation in protected areas acts on two fronts, in general, disconnected: social and biophysical. In practice, the dichotomy between impact and safety managements, using disparate tools, inhibits one or another tool according to the vision and capacity of the management teams. This work aims to systematize an integrative vision where the quality of the visitation experience and the subsequent direct or indirect environmental changes can be weighted, evaluated and managed simultaneously within a Security and Impact Management System.